TEMPO-Catalyzed Oxidative Amidation of Alcohols via Hexafluoroisopropyl Esters - Vatèle, Jean-Michel (Synlett, 2015)
Stepwise oxidative amidation of alcohols using trichloroisocyanuric acid, a catalytic amount of TEMPO in combination with pyridine and hexafluoroisopropyl (HFIP) alcohol followed by amines is described. This procedure used HFIP esters as activating esters which were found to be very efficient acylating agents for amide bond formation. This process is compatible with a number of functional groups and acid-sensitive protecting groups.
Keywords: alcohols; amidation; hexafluoroisopropyl esters; tandem oxidative process; TEMPO